2006
DOI: 10.1016/j.visres.2005.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral refraction along the horizontal and vertical visual fields in myopia

Abstract: Peripheral refractions were measured to 35 degrees eccentricity using a free-space autorefractor in young adult emmetropic and myopic subjects. Refractions were measured along horizontal and vertical visual fields for 116 subjects and a 43 subject subset, respectively. Along the horizontal visual field, peripheral myopic shifts in spherical equivalent M of emmetropes changed to relative hypermetropic shifts in the myopes, there were temporal-nasal asymmetries of 90 degrees to 180 degrees astigmatism J(180) whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

41
246
6
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 244 publications
(298 citation statements)
references
References 23 publications
41
246
6
5
Order By: Relevance
“…Similar to spectacles and contact lenses, Ortho-K creates sharp focus on the central area of the retina (macula and peri-macular area). But, peripheral to the macular area, while spectacle and contact lens correction creates relative peripheral hyperopia, Ortho-K creates relative peripheral myopia [51][52][53][54][55][56]. This relative peripheral myopic defocus inhibits the signaling for the eye to elongate [50].…”
Section: How Ortho-k Slows Myopic Progressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to spectacles and contact lenses, Ortho-K creates sharp focus on the central area of the retina (macula and peri-macular area). But, peripheral to the macular area, while spectacle and contact lens correction creates relative peripheral hyperopia, Ortho-K creates relative peripheral myopia [51][52][53][54][55][56]. This relative peripheral myopic defocus inhibits the signaling for the eye to elongate [50].…”
Section: How Ortho-k Slows Myopic Progressionmentioning
confidence: 99%
“…Individually designing Ortho-K lenses for optimal myopia control may involve creation of custom lens profiles generated from baseline measurements of posterior retinal shape and peripheral refraction [52][53][54][55][56]. The ideal amount and location of the relative peripheral myopia required for optimal myopia control is not known at this time [57].…”
Section: The Future Of Myopia Control With Ortho-kmentioning
confidence: 99%
“…While the central refraction difference between the two groups was not significantly different, this may be because of the small number in their progressing group; the initial mean refraction for the progressing group was about 1.4 D more myopic than that of the non-progressing group, and this is expected to give more hyperopic relative peripheral defocus [2][3][4]. The similar axial length between the groups means little without information about the gender distribution, because males have about 0.5 mm longer axial lengths than females of similar refractions and age [5][6][7]; also, again, there may have been insufficient children in this group to show a real difference.…”
mentioning
confidence: 81%
“…16,18 Considerable human research is being carried out to study the hypothesis that defocus and astigmatism in the retinal periphery may influence the development and progression of myopia. These studies [12][13][14][15][16][17][18][19][20][21] have reported diverse peripheral refraction patterns with various levels of ametropia. However, most suggest that emmetropes and hypermetropes have relative myopic shifts in the periphery, while myopes have relative hypermetropic shifts.…”
Section: Introductionmentioning
confidence: 99%
“…24,[26][27][28][29][30] Previous research has revealed that myopic progression is probably associated with several factors like environment, studies, lifestyle, genetics, near work [35][36][37][38][39][40][41][42][43][44][45][46] as well as with the optical defocus theory. It is now widely acknowledged that the defocus in the periphery of myopic eyes may stand a stimulus for the axial growth of the eye [17][18][19][20][21] but none has looked into the type of myopia, whether refractive or axial, at the start/detection stage and its capability to provoke eye growth.…”
Section: Introductionmentioning
confidence: 99%